England and Iberia in the Middle Ages, 12th-15th Century
XIII, 250 p.
Keywords: This groundbreaking interdisciplinary collection of essays by American, British, and Iberian scholars examines the literary, historical, and artistic exchanges between England and Iberia from the Twelfth to Fifteenth century.